Complete mitochondrial genome suggests diapsid affinities of turtles - Zardoya, Rafael (The National Academy of Sciences, 1998)
Despite more than a century of debate, the evolutionary position of turtles (Testudines) relative to other amniotes (reptiles, birds, and mammals) remains uncertain. One of the major impediments to resolving this important evolutionary problem is the highly distinctive and enigmatic morphology of turtles that led to their traditional placement apart from diapsid reptiles as sole descendants of presumably primitive anapsid reptiles. To address this question, the complete (16,787-bp) mitochondrial genome sequence of the African side-necked turtle (Pelomedusa subrufa) was determined. This molecule contains several unusual features: a (TA)(n) microsatellite in the control region, the absence of an origin of replication for the light strand in the WANCY region of five tRNA genes, an unusually long noncoding region separating the ND5 and ND6 genes, an overlap between ATPase 6 and COIII genes, and the existence of extra nucleotides in ND3 and ND4L putative ORFs. Phylogenetic analyses of the complete mitochondrial genome sequences supported the placement of turtles as the sister group of an alligator and chicken (Archosauria) clade. This result clearly rejects the Haematothermia hypothesis (a sister-group relationship between mammals and birds), as well as rejecting the placement of turtles as the most basal living amniotes. Moreover, evidence from both complete mitochondrial rRNA genes supports a sister-group relationship of turtles to Archosauria to the exclusion of Lepidosauria (tuatara, snakes, and lizards). These results challenge the classic view of turtles as the only survivors of primary anapsid reptiles and imply that turtles might have secondarily lost their skull fenestration.